Invalid Use of Extraordinary Form of Marriage: Canon 1116 - Huels, John M. (Roman replies and CLSA advisory opinions 1996, 1996)
A laicized priest in our diocese is a widower from a marriage he contracted in the 1970s. Recently, he requested permission from the bishop to enter a secret marriage, giving as a reason the fact that he and his intended spouse had limited retirement income and would suffer a loss of financial benefits if they were publicly married with a marriage license. The bishop denied his request. He has now written to the bishop asking him to record in the secret archive his marriage celebrated according to the extraordinary form of canon 1116, claiming that they would have been gravely inconvenienced by a public ceremony resulting in a loss of income, and that no priest or deacon was “morally available.” He cited your book, The Pastoral Companion, as sanctioning this approach. I checked and noticed that you did address the issue of moral unavailability, but I am doubtful whether this was a correct application of the principle.